Proceeding of Liverpool Singularities Symposium II [papers] - Symposium on Singularities of Smooth Manifolds and Maps, University of Liverpool, Liverpool, September 1969-August 1970; Wall, C T C (Berlin : Springer-Verlag, 1971)
41